The evolution of laws and social conceptions concerning adoption: from the 1960s to the inclusion of single parents in intercountry adoption. Educational considerations - Stefania Lorenzini (Educazione Interculturale)
Sentence No. 33, issued by the Constitutional Court on 21 March 2025, opens up the possibility for singles to apply to the Juvenile Courts to be assessed for access to intercountry adoption, where they had been excluded for decades, except in special cases. In the light of this novelty (not unanimously shared but long awaited by many), the contribution takes the opportunity to focus on some crucial passages in the evolution of national and international adoption legislation and the related transformations in the conceptions of family and adoptive filiation, up to the aforementioned judgment. And to turn attention on an educational level to some aspects of single-parent and adoptive parenting.